Prevalence of virulence genes among bulgarian nosocomial and cystic fibrosis isolates of Pseudomonas aeruginosa - Mitov,Ivan (2010)
The aim of this study was to evaluate the prevalence of some virulence genes among 202 Pseudomonas aeruginosa isolates from cystic fibrosis (CF) patients (n=42) and non-CF in-patients (n=160) and to analyze the values according to the patient groups, infection localization and antimicrobial resistance. The following frequencies in all studied strains were established: algD (encoding GDP-mannose 6-dehydrogenase AlgD) - 91.1%, pilB (type IV fimbrial biogenesis protein PilB) - 23.8%, nan1 (neuraminidase) - 21.3%, lasB (elastase LasB) - 100%, plcH (haemolytic phospholipase C precursor) - 91.6%, exoS (exoenzyme S) - 62.4%, and exoU (exoenzyme U) - 30.2%. The prevalence of nan1 was significantly higher (P<0.01) in CF isolates (38.1%) than that in non-CF isolates (16.9%). The nan1-positive CF strains were cultured from 16 patients with recurrent lung exacerbations. This study revealed a statistically significant difference (P<0.01) between the portion of multidrug-resistant (MDR) nosocomial P. aeruginosa strains containing a large number (≥5) of virulence genes (38.1%) and the respective part of non-MDR isolates (17.6%). Moreover, pilB, exoU and nan1 manifested a higher spread (P<0.001) among MDR than in non-MDR strains (respectively, 39.1% vs. 13.2%; 40.2% vs. 17.7% and 26.1% vs. 4.4%). In conclusion, the dissemination of nan1 in CF isolates was moderate and correlated with the lower proportion of patients with lung exacerbations. The molecular-genetic detection of this gene may be used as an indirect measure of CF pulmonary disease evolution. Simultaneous determination of virulence factors and antimicrobial resistance is the contemporary approach for examination of the microbiological aspects of infections caused by P. aeruginosa.